INTERRELIGIOUS DIALOGUE: PAST AND PRESENT A CRITICAL APPRAISAL - V.F. Vineeth (Journal of Dharma, 1994)
Rerigion is a way of relating oneself to God, to the Ultimate or to the meaningfulness of one’s own life. As relatedness to the Ultimate it also becomes a way of relationship to others through whom the Ultimate is seen or experienced. The nature of this relation is coloured by the nature of faith by which the religion is characterized. The reality today is that both in the E.astand the West we are living with people of other faiths. What was every day experience in many parts of the East is becoming a matter of daily experience in the West. In the classroom, in the factory, in the city bus and in one’s own neighburhood, one meets followers of other faiths. Their sincerity, their authenticity, their commitment to their own religion and their moral excellence is beginning to affect one’s own self-understanding and the understanding of his religion. Inter-religious experience is increasingly becoming part of any religious experience.